A Dual Gender Rare Case with 47,XY, + 18/46,XX Karyotype: Chimera or Mosaic? - Ankathil, Ravindran; Eva, Foong; Bakar, Zulaikha Abu; Yunus, Nazihah Mohd; Nawi, Nurul Alia; Annuar, Aziati; Ting, Cheng Yi; Sulong, Sarina (Journal of Child Science, 2021)
Our objective is to report one rare case of dual gender chimerism involving abnormal male trisomy 18 and normal female karyotype. The baby was born full term with birth weight of 1.8 kg, not vigorous with light meconium stained liquor and Apgar score of 51, 85 and 910. Parents are 40 years old and mother is G6P5 + 1. The baby had clinical features of Edwards syndrome, and a blood sample was sent to Human Genome Centre, Universiti Sains Malaysia, Malaysia for cytogenetic analysis. Conventional cytogenetic analysis results showed two distinct sex discordant genetic cell lines XY and XX in 90:10 ratio. The male genetic cell line XY also showed trisomy 18 (47,XY, + 18) consistent with clinical diagnosis of male Edwards syndrome, whereas the second genetic cell line showed normal 46,XX female. The present case was reported as dual gender chimera with chi 47,XY, + 18/46,XX karyotype pattern. To the best of available knowledge, dual gender chimerism with abnormal male trisomy 18 and normal female karyotype has not been reported so far, and this case is reported for its rarity and as the first report.
Keywords: chimerism; dual gender; liveborn; trisomy 18